Anti‐IL‐5 therapies for chronic obstructive pulmonary disease - Donovan, Tim (Cochrane Database Syst Rev, 2020)
BACKGROUND: Exacerbations of chronic obstructive pulmonary disease (COPD) are a major cause of hospital admissions, disease‐related morbidity and mortality. COPD is a heterogeneous disease with distinct inflammatory phenotypes, including eosinophilia, which may drive acute exacerbations in a subgroup of patients. Monoclonal antibodies targeting interleukin 5 (IL‐5) or its receptor (IL‐5R) have a role in the care of people with severe eosinophilic asthma, and may similarly provide therapeutic benefit for people with COPD of eosinophilic phenotype. OBJECTIVES: To assess the efficacy and safety of monoclonal antibody therapies targeting IL‐5 signalling (anti‐IL‐5 or anti‐IL‐5Rα) compared with placebo in the treatment of adults with COPD. SEARCH METHODS: We searched the Cochrane Airways Trials Register, CENTRAL, MEDLINE, Embase, clinical trials registries, manufacturers' websites, and reference lists of included studies. Our most recent search was 23 September 2020. SELECTION CRITERIA: We included randomised controlled trials comparing anti‐IL‐5 therapy with placebo in adults with COPD. DATA COLLECTION AND ANALYSIS: Two review authors independently extracted data and analysed outcomes using a random‐effects model.The primary outcomes were exacerbations requiring antibiotics or oral steroids, hospitalisations due to exacerbation of COPD, serious adverse events, and quality of life. We used standard methods expected by Cochrane. We used the GRADE approach to assess the certainty of the evidence. MAIN RESULTS: Six studies involving a total of 5542 participants met our inclusion criteria. Three studies used mepolizumab (1530 participants), and three used benralizumab (4012 participants). The studies were on people with COPD, which was similarly defined with a documented history of COPD for at least one year. We deemed the risk of bias to be generally low, with all studies contributing data of robust methodology. Mepolizumab 100 mg reduces the rate of moderate or severe exacerbations by 19% in those with an eosinophil count of at least 150/μL (rate ratio (RR) 0.81, 95% confidence interval (CI) 0.71 to 0.93; participants = 911; studies = 2, high‐certainty evidence). When participants with lower eosinophils are included, mepolizumab 100 mg probably reduces the exacerbation rate by 8% (RR 0.92, 95% CI 0.82 to 1.03; participants = 1285; studies = 2, moderate‐certainty evidence). Mepolizumab 300 mg probably reduces the rate of exacerbations by 14% in participants all of whom had raised eosinophils (RR 0.86, 95% CI 0.70 to 1.06; participants = 451; studies = 1, moderate‐certainty evidence); the evidence was uncertain for a single small study of mepolizumab 750 mg. In participants with high eosinophils, mepolizumab probably reduces the rate of hospitalisation by 10% (100 mg, RR 0.90, 95% CI 0.65 to 1.24; participants = 911; studies = 2, moderate‐certainty evidence) and 17% (300 mg, RR 0.83, 95% CI 0.51 to 1.35; participants = 451; studies = 1, moderate‐certainty evidence). Mepolizumab 100 mg increases the time to first moderate or severe exacerbation compared to the placebo group, in people with the eosinophilic phenotype (hazard ratio (HR) 0.78, 95% CI 0.66 to 0.92; participants = 981; studies 2, high‐certainty evidence). When participants with lower eosinophils were included this difference was smaller and less certain (HR 0.87, 95% CI 0.75 to 1.0; participants = 1285; studies 2, moderate‐certainty evidence). Mepolizumab 300 mg probably increases the time to first moderate or severe exacerbation in participants who all had eosinophilic phenotype (HR 0.77, 95% CI 0.60 to 0.99; participants = 451; studies = 1, moderate‐certainty evidence). Benralizumab 100 mg reduces the rate of severe exacerbations requiring hospitalisation in those with an eosinophil count of at least 220/μL (RR 0.63, 95% CI 0.49 to 0.81; participants = 1512; studies = 2, high‐certainty evidence). Benralizumab 10 mg probably reduces the rate of severe exacerbations requiring hospitalisation in those with an eosinophil count of at least 220/μL (RR 0.68, 95% CI 0.49 to 0.94; participants = 765; studies = 1, moderate‐certainty evidence). There was probably little or no difference between the intervention and placebo for quality of life measures. Where there were differences the mean difference fell below the pre‐specified minimum clinically significant difference. Treatment with mepolizumab and benralizumab appeared to be safe. All pooled analyses showed that there was probably little or no difference in serious adverse events, adverse events, or side effects between the use of a monoclonal antibody therapy compared to placebo. AUTHORS' CONCLUSIONS: We found that mepolizumab and benralizumab probably reduce the rate of moderate and severe exacerbations in the highly selected group of people who have both COPD and higher levels of blood eosinophils. This highlights the importance of disease phenotyping in COPD, and may play a role in the personalised treatment strategy in disease management. Further research is needed to elucidate the role of monoclonal antibodies in the management of COPD in clinical practice. In particular, it is not clear whether there is a threshold blood eosinophil level above which these drugs may be effective. Studies including cost effectiveness analysis may be beneficial given the high cost of these therapies, to support use if appropriate.